THE NOTION OF NATIONAL MINORITY IN THE RUSSIAN LAW - A. Skorobogatov (Russian Journal of Economics and Law)
The article is dedicated to the analysis of the usage of term "national minority" in the Russian law. The author has viewed the Russian constitutional acts dedicated to the determination of the legal status and national minorities' rights protection, and revealed the features of the usage of the mentioned term in them. Special attention is paid to the ambiguity of the legislative usage of the term "national minority". The research is made with the support of the Russian Humanities Scientific Fund. RHSF, grant № 07-03-29302а/В.